English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve by substitution:
1) 3x - 2y = 8
-6x + 4y = -16

2) 2x + y = 9
x - 3y = 22

2006-11-27 12:18:45 · 5 answers · asked by GMEN 1 in Science & Mathematics Mathematics

5 answers

2. y = -2x+9

x - 3(-2x +9) = 22

x - 6x - 27 = 22

-5x - 27 = 22

-5x = 49

x = - 49/5

Do the same for #1

2006-11-27 12:23:09 · answer #1 · answered by J3Buckets 2 · 0 0

3x-2y =8
-6x +4y = -16
Multiply the first equation by -2 and get
-6x+4y = -16, which is same as second equation.
The two equations are the same so no solution exists

2x +y =9
x -3y = 22 Multiply 1st equation by 3 to get:
6x +3y =27 Add this new equation to second equation, getting
7x=49
x=7
Substitute x=7 into 1st equation, getting:
2(7) +y =22
14 + y = 22
y = 22 - 14 =8

2006-11-27 20:31:23 · answer #2 · answered by ironduke8159 7 · 0 0

1) can be any number

2) 2x + y = 9
x - 3y = 22

multiply the the top by (-3) so the y's can cancel out

[2x + y = 9] x 3
x - 3y = 22

-6x - 3y = -27
x - 3y = 22

now add 2 problems together and solve for x

-5x = -5
x = 1

now that you have x, plug that into either of the original problems to find y

2(1) + y = 9
2 + y = 9
y = 7

x = 1, y = 7 is your answer

2006-11-27 20:24:26 · answer #3 · answered by dizzawg16 3 · 0 0

1. any real #,
2.x = 7

2006-11-27 20:21:51 · answer #4 · answered by dg24 2 · 0 0

its B

2006-11-27 20:19:33 · answer #5 · answered by kingbling169 1 · 0 0

fedest.com, questions and answers